2015
DOI: 10.1101/023549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic signatures of experimental adaptation to antimicrobial peptides inStaphylococcus aureus

Abstract: ObjectivesThe evolution of resistance against antimicrobial peptides has long been considered unlikely due to their mechanism of action, yet experimental selection with AMPs results in rapid evolution of resistance in several species of bacteria. Although numerous studies have utilized mutant screens to identify loci that determine AMP susceptibility, there is a dearth of data concerning the genomic changes which accompany experimental evolution of AMP resistance.MethodsUsing genome re-sequencing we analysed t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
1
4
2
Order By: Relevance
“…We have previously shown that evolution of resistance towards the AMP melittin in S. aureus JLA513 is associated with nonsense mutations in ytrA . Here we find that the most frequent ytrA mutation is identical to the stop-gain mutation described in S. aureus JLA513 12 . In S. aureus , the ytr operon is induced by cationic AMPs 32 and encodes a putative GntR-family repressor (YtrA) as well as two ABC transporters.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…We have previously shown that evolution of resistance towards the AMP melittin in S. aureus JLA513 is associated with nonsense mutations in ytrA . Here we find that the most frequent ytrA mutation is identical to the stop-gain mutation described in S. aureus JLA513 12 . In S. aureus , the ytr operon is induced by cationic AMPs 32 and encodes a putative GntR-family repressor (YtrA) as well as two ABC transporters.…”
Section: Discussionsupporting
confidence: 63%
“…While our assessment is based on the Jaccard-Distance, it is noteworthy that all strains have one of two resistance-associated mutations. This is much lower than the variation observed in a previous study in S. aureus against a panel of antimicrobial peptides originating from different organisms 12 .…”
Section: Lack Of Parallel Evolutioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In a recent experimental evolution study investigating S. aureus resistance evolution against three different AMPs from different organisms (melittin, pexiganan and iseganan) 12 , we found a range of mutations associated with resistance 13 . These mutations were not specific for different AMPs.…”
Section: Introductionmentioning
confidence: 86%
“…Such defence cocktails often contain a high abundance of AMPs that are not known to be effective against the infectious agent, (Barribeau, Sadd, du Plessis, & Schmid‐Hempel, ; Makarova et al., ; Yokoi, Ito, Minakuchi, Toshiharu, & Miura ), despite the capacity of the insect immune system to mount‐specific immune responses (Kounatidis & Ligoxygakis, ). Also, the expression of AMPs comes at a metabolic cost (Johnston, Dobson, & Rolff, ; Poulsen, Bot, Nielsen, & Boomsma, ).…”
Section: Introductionmentioning
confidence: 99%